DIGESTIBILITY NUTRIENTS OF BALI CATTLE FED RATION FERMENTED LIGNOCELLULOLYTIC BACTERIA INOCULANT OF CATTLE COLON AND ORGANIC WASTE - M., Sobari; Mudita, I M.; Cakra, I G. L. O. (Jurnal Peternakan Tropika, 2018)
The research aims to evaluated the effect of fed ration fermented by superior lignocellulolytic bacteria of bali cattle colon and organic waste towards the digestibility of nutrients bali cattle and to know the formula of inoculant which is able to produce ration with better nutrient content. This research uses the latin square design with four treatments and four replicates. The treatments consists of: rations fermented without superior inoculant (PSB0), fermented rations with the best bacteria culture 1, 2 of bali cattle colon and best 1, 2 of organic waste (PSB1), fermented rations with the best bacteria culture 1, 2 of bali cattle colon and best 1 of organic waste (PSB2), fermented rations with the best bacteria culture 1 of bali cattle colon and best 1, 2 of organic waste (PSB3). The observed variables were dry matter digestibility, organic matter digestibility, crude fiber digestibility, crude protein digestibility, digested dry matter amount, digested organic matter amount, digested crude fiber amount and digested amount of crude protein. The results showed that the digestibility of nutrient rations PSB1, PSB2 and PSB3 significantly (P<0.05) higher than the ration PSB0. The amount of dry matter and organic matter digested ration PSB1, PSB2 and PSB3 have different values ??not significantly (P>0.05) compared with PSB0 rations, whereas the amount of crude fiber and crude protein digested in PSB1, PSB2 and PSB3 rations has significantly (P<0.05) higher than PSB0. Based on the results of this study it can be concluded that fermentation of rations using superior inoculant from bali cattle colon and organic waste can improve the digestibility of nutrients and the amount of digested nutrients in rations and PSB1 rations shows the highest digestibility of nutrient and nutrient digested compared than other rations. Key words: Cattle Colon, Organic Waste, Inoculant, Nutrients Digestibility.